Introduction of a Luminophore into Generic Polymers via Mechanoradical Coupling with a Prefluorescent Reagent. Issue 29 (9th June 2021) - Kubota, Koji; Toyoshima, Naoki; Miura, Daiyo; Jiang, Julong; Maeda, Satoshi; Jin, Mingoo; Ito, Hajime
Abstract: Herein, we report a novel strategy for introducing a luminophore into generic polymers facilitated by mechanical stimulation. In this study, polymeric mechanoradicals were formed in situ under ball‐milling conditions to undergo radical–radical coupling with a prefluorescent nitroxide‐based reagent in order to incorporate a luminophore into the polymer main chains via a covalent bond. This method allowed the direct and conceptually simple preparation of luminescent polymeric materials from a wide range of generic polymers such as polystyrene, polymethyl methacrylate, and polyethylene. These results indicate that the present mechanoradical coupling strategy may help to transform existing commodity polymers into more valuable functional materials. Abstract : Polymeric mechanoradicals were formed in situ under ball‐milling conditions to undergo radical–radical coupling with a prefluorescent nitroxide‐based reagent in order to incorporate a luminophore into the polymer main chains via a covalent bond. The method allows the direct and conceptually simple preparation of luminescent polymeric materials from a wide range of generic polymers such as polystyrene, polymethyl methacrylate, and polyethylene.